Immunopathogenic and Neurological Mechanisms of Canine Distemper Virus - Otávio Valério Carvalho; Clarisse Vieira Botelho; Caroline Gracielle Torres Ferreira; Paulo Oldemar Scherer; Jamária Adriana Pinheiro Soares-Martins; Márcia Rogéria Almeida; Abelardo Silva Júnior (Advances in Virology)
Canine distemper is a highly contagious viral disease caused by the canine distemper virus (CDV), which is a member of the Morbillivirus genus, Paramyxoviridae family. Animals that most commonly suffer from this disease belong to the Canidae family; however, the spectrum of natural hosts for CDV also includes several other families of the order Carnivora. The infectious disease presents worldwide distribution and maintains a high incidence and high levels of lethality, despite the availability of effective vaccines, and no specific treatment. CDV infection in dogs is characterized by the presentation of systemic and/or neurological courses, and viral persistence in some organs, including the central nervous system (CNS) and lymphoid tissues. An elucidation of the pathogenic mechanisms involved in canine distemper disease will lead to a better understanding of the injuries and clinical manifestations caused by CDV. Ultimately, further insight about this disease will enable the improvement of diagnostic methods as well as therapeutic studies.